Системи технічного зору в задачах розпізнавання образів - Дрождік, О. О. (ХНУРЕ, 2025)
The work reflects the current state of research and the main directions of work. In the future, this work can be expanded towards the creation of a comprehensive vision system that combines object recognition, their classification and spatial analysis of the scene. Additionally, it is worth considering the use of stereo cameras to build a three-dimensional model of the environment, which will significantly expand the functionality of the mobile robot. Such improvements will open up new opportunities for the use of such systems not only in industry, but also in the field of environmental monitoring, search and rescue operations and "smart" logistics.
Keywords: система технічного зору; розпізнавання образів